Effects of deformation on the microstructure of a Cu-Al-Be shape memory alloy - Balo, SN; Ceylan, M; Aksoy, M (Elsevier Science Sa, 2001)
The austenite phase structure of a shape memory alloy with the composition Cu-11.8wt.%Al-0.47wt.%Be has been determined as a DO, superlattice by using X-ray diffraction techniques. The effects of compressive loading on the memory behaviour and the phase transformation properties have been investigated. The annihilation of shape memory behaviour by loading at 113.6 kg mm(-2) compressive stress was determined from the differential scanning calorimetry (DSC) curves. The occurrence of martensite phase transformations depending on increasing stress level has also been determined from DSC curves, X-ray diffractograms and scanning electron microscope observations. For a stress of 113.6 kg mm(-2) and more, as seen for 125.7 kg mm(-2), martensite phase stabilisation was also seen. (C) 2001 Elsevier Science B.V. All rights reserved.
Keywords: phase transformation; martensite; shape memory; stress level